2017
DOI: 10.1051/0004-6361/201628485
|View full text |Cite
|
Sign up to set email alerts
|

Polarimetric survey of main-belt asteroids

Abstract: Aims. We present the first results of a polarimetric survey of main-belt asteroids at Complejo Astronómico El Leoncito (Casleo), San Juan, Argentina. The aims of this survey are to increase the database of asteroid polarimetry, to estimate diversity in polarimetric properties of asteroids that belong to different taxonomic classes, and to search for objects that exhibit anomalous polarimetric properties, similar to those shown by the asteroid (234) Barbara. Methods. The data were obtained with the Torino and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…This includes computations of the position angle of the scattering plane and of the polarization parameter P r . The overall data reduction pipeline is essentially identical to that previously used in Gil-Hutton et al (2017). As a test of the data reduction process, we analyzed the distribution of the ratio between the U component of linear polarization and its error and found that it is centered at zero, while all points differ from this value by less than a few σ, which supports the reliability of the polarimetric measurements.…”
Section: Observationsmentioning
confidence: 59%
See 2 more Smart Citations
“…This includes computations of the position angle of the scattering plane and of the polarization parameter P r . The overall data reduction pipeline is essentially identical to that previously used in Gil-Hutton et al (2017). As a test of the data reduction process, we analyzed the distribution of the ratio between the U component of linear polarization and its error and found that it is centered at zero, while all points differ from this value by less than a few σ, which supports the reliability of the polarimetric measurements.…”
Section: Observationsmentioning
confidence: 59%
“…Figure 2 shows the observations obtained for three T -types and six D-types objects (four and eight observations, respectively), and it seems that the D-types show a bimodality in their polarimetric behavior where two asteroids, (565) Marbachia and (1481) Tubingia, seem to have phase-polarization curves with large inversion angles. Recently, Gil-Hutton et al (2017) reported that this polarimetric behavior is also observed for (2579) Spartacus, a V-type object, so if this bimodality is confirmed in the future for D-types, it would indicate that the Barbarian group of asteroids is present in different taxonomic classes and is not an exclusivity of L-, Ld-, and K-types.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…4). We used the h values of asteroids provided in the catalog of the asteroid polarization curves (Gil-Hutton et al 2017). The applied slope h values from the catalog are determined in the V band.…”
Section: Appendix A: Usage Of the Terms Comets And Asteroidsmentioning
confidence: 99%